Courseware for home decoration (HomeyCo) / Sumira Abdullah - Abdullah, Sumira (2014)
The existence of the development in the information and communication technology (ICT), multimedia has been greatly applicable in the field of learning. Animation, video and audio are integrated with instruction in order to create a more supportive, interesting and conducive learning environment. Nowadays, people tend to use the more attractive materials in their learning process. The courseware for home decoration is less widespread compared to the other courseware. Users will face difficulties to do a survey when they want to decorate a house. This courseware was developed to help the user while decorating a house. HomeyCo was provided with a lot of tips and tricks that are useful to the users while decorating a house. This courseware was developed with using ADDIE model. It consists of five cyclical phases which are analysis, design, development, implementation and evaluation. While doing this project, the formative evaluation and summative evaluation had been done to ensure that this courseware can meet the user’s requirements. After done with the development phase, the questionnaires were distributed to 31 respondents to conduct the evaluation process of the project. Most of the respondents gave the positive feedback and satisfied with this courseware. Most of them agreed that they were clearly understand the goal of the homepage of this courseware and the performance of this courseware works very well. The respondents also agreed that the use of terms throughtout this courseware were good and easily understandable and they also would like to use this courseware frequently. Some of them also agreed that by using this courseware, it would help them a lot in decorating a house. HomeyCo had already achieved its objectives and the future enchancements will be done from time to time to satisfy the user’s needs